Severe clear eaudiobook - Woods, Stuart (Stone Barrington, 2016)
New York Times best-selling author Stuart Woods is at the top of his game with Severe Clear —his 50th published novel, and the 24th featuring his fan-favorite creation, Stone Barrington. On hand for the grand opening of the new Arrington hotel, Stone is alerted to a terrorist plot threatening the gala. Determined to end this threat before anyone dies, Stone enlists the aid of a few friends from the CIA.